0

# 3*(2x^2+6x+3)

Evaluate expression I want the answer help me

### 3 Answers by Expert Tutors

Yossi Y. | Electronic Engineering Background and Teaching/Tutoring ExperienceElectronic Engineering Background and Te...
5.0 5.0 (4 lesson ratings) (4)
0
3(2X^2 + 6X +3) = 6X^2 + 18X + 9

This is the quadratic equation  aX^2 + bX + C

Where X is the unknown variable to be resolved, and  a,b,c are constants

Soluttion:

X 1,2

3(2X^2 + 6X +3) = 6X^2 + 18X + 9

This is the quadratic equation aX^2 + bX + C

Where X is the unknown variable to be resolved, and a,b,c are constants

Solutions:

X12 = ( - b +- √ (b^2 – 4ac) )/2a

Solution 1:

X1 = ( -18 + √ (18^2 – 4*6*9) )/2*6 = ( -18 + √ (324 – 216) )/12 = ( -18 + √ (108) )/12

X1 = -18/12 + √ (108)/12

Solution 2:

X2 = ( -18 - √ (18^2 – 4*6*9) )/2*6 = ( -18 - √ (324 – 216) )/12 = ( -18 - √ (108) )/12
X2 = -18/12 - √ (108)/12

Farid S. | Experienced Math TutorExperienced Math Tutor
4.8 4.8 (32 lesson ratings) (32)
0
This is actually pretty straight forward.  Just multiply 3 all the way through.

So, we get 6x^2 + 18x + 9.
Donald D. | Innovative Math Tutor Elementary through College Level SubjectsInnovative Math Tutor Elementary through...
0
6x^2+18x+9